The gates [videorecording (DVD)] - Hall, Stephen; Reynolds, Tim; Rhys-Davies, John; Brake, Richard, 1964-; Yare, Michael (101 Films, 2023)
In 1890s London, death-row inmate William Colcott places a curse on the prison and its inhabitants before his execution. Two paranormal investigators must stop William's spirit from escaping the prison and unleashing the gates of hell on London.